ASSISTANCE IN THE IMPLEMENTATION OF SERVICE TO THE THEMATIC KKM STUDENT COMMUNITY IN SIKETUG VILLAGE, CIOMAS DISTRICT, SERANG REGENCY - Anton Nasrullah; Aghi Septian Zikry; Gina Mutiara Rosdalina; Adisti Febri Asharani; Saadah Saadah; Anggita Apriyani Putri; Rani Puspa; Melinda Putri Mubarika (Yayasan Education and Social Center, 2022)
Thematic Student Work Lectures (KKM Thematic) of Bina Bangsa University carry out community service tasks to help developers with work programs that have been mutually agreed upon in Siketug village, Ciomas district, Serang-Banten. The purpose of the implementation is so that students can; First, deepen appreciation of how to think and work in developing eight activity programs, providing skills and taking an active role in village/ development; Second, students have a high sense of sensitivity to the problems and difficulties faced by the community in community empowerment. Third, it is a solution to dealing with every problem in society. Third, to produce students as motivators, problem solvers, and facilitators (companions). Implementing the activities is to conduct socialization, mentoring, and empowerment of rural communities by directly involving the Siketug village community, Ciomas District. The achievements in these activities are students; First, it has been able to deepen appreciation of how to think and work in developing eight program activities, providing skills and taking an active role in village development; Second, students can have a high sense of sensitivity to the problems and difficulties faced by the community in community empowerment. Third, students can have a solution to dealing with every problem in society. Third, produce students as motivators, problem solvers, and facilitators (companions) in Siketug Village, Ciomas District, Serang Regency, Banten Province